THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS A MODERATING VARIABLE - Ndaru Murni Ayuningtyas; Suwarno Suwarno; Ahmad Basri (Jurnal Interprof, 2025)
This research quantitatively investigates the roles of transformational leadership and career development in shaping employee performance, with employee motivation acting as a moderating factor, within the Department of Communication, Informatics, Statistics, and Encryption (Kominfotiksan) of Lubuklinggau City. The study’s focus on Lubuklinggau’s Kominfotiksan Office arises from observed deficiencies in motivational dynamics: leadership offers limited recognition of employees’ completed tasks, attendance at training sessions remains low, and strategic departmental objectives do not translate effectively into on-the-ground actions, thereby compromising the quality of public information services. Furthermore, a reluctance to cultivate digital competencies persists, stemming from scarce training and a widespread underappreciation of technological fluency. The research population encompasses all Kominfotiksan Office personnel, and a purposive sample of 47 employees was drawn. The analysis employs multiple linear regression augmented by Moderated Regression Analysis (MRA). Findings indicate that both transformational leadership and structured career development exert statistically significant influences on performance, whether in isolation or collectively. Motivation, in turn, amplifies the effects of both independent variables on employee performance, confirming its role as a reinforcing moderator.